2015
DOI: 10.1080/15476286.2015.1017208
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-200b and microRNA-200c promote colorectal cancer cell proliferation via targeting the reversion-inducing cysteine-rich protein with Kazal motifs

Abstract: MicroRNA-200b and microRNA-200c (miR-200b/c) are 2 of the most frequently upregulated oncomiRs in colorectal cancer cells. The role of miR-200b/c during colorectal tumorigenesis, however, remains unclear. In the present study, we report that miR-200b/c can promote colorectal cancer cell proliferation via targeting the reversion-inducing cysteine-rich protein with Kazal motifs (RECK). Firstly, bioinformatics analysis predicted RECK as a conserved target of miR-200b/c. By overexpressing or knocking down miR-200b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…In gastric, breast, esophageal and pancreatic cancer cells, RECK gene expression is low and usually accompanied by abnormal methylation (26,27). The present study demonstrated that casticin upregulated RECK mRNA and protein expression in MGC803 gastric cancer cells.…”
Section: Discussionsupporting
confidence: 52%
“…In gastric, breast, esophageal and pancreatic cancer cells, RECK gene expression is low and usually accompanied by abnormal methylation (26,27). The present study demonstrated that casticin upregulated RECK mRNA and protein expression in MGC803 gastric cancer cells.…”
Section: Discussionsupporting
confidence: 52%
“…33 While this is only a single study, it highlights the fact that microRNAs can target multiple pathways and may have conflicting effects on tumor signaling. This led to downsteam activation of SKP2 and CDKN1B, which promote tumor proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The reversion-inducing cysteine-rich protein with Kazal motifs (RECK) is considered as a tumour suppressor associated with low invasiveness and favourable prognosis in cancers [27][28][29][30] and suppresses tumour invasive and metastatic potential [31,32]. Moreover, multiple miRNAs including miR-21, miR-15a, miR-200b/c, miR-96 and miR-221 have been proved to promote tumour growth and metastasis via targeting RECK [33][34][35][36][37]. Intriguingly, we also identified RECK as a direct target of miR-15b in PCa cells and verified that it was negatively associated with miR-15b expression in PCa tissues.…”
Section: Discussionmentioning
confidence: 99%